Symptomatic Acute Hepatitis C Infection Following a Single Episode of Unprotected Sexual Intercourse. (10th November 2016) - Butler, Benjamin; Narayan, Bhaskar; Potts, Jonathan; Emmanuel, Julian
Abstract : A previously healthy 23-year-old MSM presented with jaundice, systemic upset, and rash 2 months after a single episode of unprotected sexual intercourse. Liver biochemistry was grossly deranged, with markedly elevated transaminases and hyperbilirubinaemia. Serology was positive for genotype 1a hepatitis C virus (HCV) and in the absence of other causes, acute HCV infection was suspected. He was subsequently successfully treated with pegylated interferon and ribavirin for 24 weeks and made a full clinical and biochemical recovery.